O‘QUVChILARNING NUTQIY KOMPETENSIYALARINI RIVOJLANTIRIShDA ZAMONAVIY METODLARDAN FOYDALANISh - Sultanova, A. (SCIENCE and SOCIETY, 2025)
The article reflects on the advantages of general secondary education schools teaching grammatical materials in Uzbek language lessons and using interactive methods in this.